Rehydration Kinetics of Dehydrated Vegetables Pre-Treated By Ohmic-Blanching - Joshua Oheji Otugbeikwu; Philip Abraham Aligwe; Julius Amove (Food ScienTech Journal, 2023)
Dehydration is an irreversible process resulting in the loss of structural integrity and rehydration capacity (RC) of food products. Pretreatment methods are used to condition the tissue of vegetables for dehydration in order to reduce its effect on the structural integrity of the products. In this study, we investigated the effect of ohmic blanching as a pretreatment method and compared it with water blanching and microwave blanching. The Peleg model was used to evaluate the rehydration properties through regression analysis. The model was satisfactorily fitted with the data. However, there was a model deviation with water-blanched potato and yam. Dehydrated products pretreated by ohmic blanching compared favorably with microwave-blanching in carrots, potatoes, and yams. The RC ranged between 264.04% to 449%, 141.40% to 274.32%, and 70.46% to 155.54% in ohmic-blanched carrots, potatoes, and yams respectively.  The application of ohmic blanching in the pretreatment of vegetables showed the potential of producing dehydrated products with better rehydration properties. The implication is an improved method of hot air dehydration which is of lower cost compared to freeze-drying. The design and model of a bench-top ohmic heating device offer a portable, simple, and low-cost alternative to the otherwise more capital-intensive equipment designs.